2009
DOI: 10.1080/08990220903158797
|View full text |Cite
|
Sign up to set email alerts
|

Electrotactile stimulation on the tongue: Intensity perception, discrimination, and cross-modality estimation

Abstract: Due to its high sensitivity and conductivity, electrotactile stimulation (ETS) on the tongue has proven to be a useful and technically convenient tool to substitute and/or augment sensory capabilities. However, most of its applications have only provided spatial attributes and little is known about (a) the ability of the tongue's sensory system to process electrical stimuli of varying magnitudes and (b) how modulation of ETS intensity affects subjects' ability to decode stimulus intensity. We addressed these q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…For example, guidance of a surgical tool manipulation has been demonstrated using only TDU-based feedback [94], and tactile feedback from robots to assist spinal cord injuries has been proposed [95], along with tactile feedback of seated pressure, to prevent pressure sores [96] and to gain greater awareness of ankle joint rotation in a fatigued state [97]. The TDU as a platform technology allows virtually any kind of information to be presented to the tongue, subject to the human limits of electrotactile perception on the tongue, which are just beginning to be explored [98]. …”
Section: Selected Applicationsmentioning
confidence: 99%
“…For example, guidance of a surgical tool manipulation has been demonstrated using only TDU-based feedback [94], and tactile feedback from robots to assist spinal cord injuries has been proposed [95], along with tactile feedback of seated pressure, to prevent pressure sores [96] and to gain greater awareness of ankle joint rotation in a fatigued state [97]. The TDU as a platform technology allows virtually any kind of information to be presented to the tongue, subject to the human limits of electrotactile perception on the tongue, which are just beginning to be explored [98]. …”
Section: Selected Applicationsmentioning
confidence: 99%
“…Previous studies have been small (averaging eight participants each), and mostly centered on mapping the sensitivity of the tongue without analyzing electrotactile two-point discrimination ability (Lozano et al, 2009; Tyler et al, 2009; Wilson et al, 2012). These studies indicate that anterior-medial tongue regions have lower thresholds for electrotactile stimulation relative to posterior regions and sensitivity to electrotactile stimulation varies widely between individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group and others have shown that the tongue can be used as an effective interface for sending signals to the central nervous system (Chebat et al 2007; Bach-y-Rita and Kercel 2003; Sampaio et al 2001; Bach-y-Rita et al 1998). Compared to the skin, the tongue provides an inviting target for electrical neurostimulation due to the high electrolyte content of saliva, allowing for low-impedance electrical input, and the high density of sensory receptors permitting reasonably high throughput of incoming signals while preserving a relatively large dynamic range (Lozano et al 2009). Additionally, because tongue neurostimulation is non-invasive, it avoids a major drawback of other commonly-used types of electrical neurostimulation such as vagal nerve and deep brain stimulation while exhibiting less non-specific activation than other non-invasive modalities such as transcranial magnetic or direct current stimulation.…”
Section: Introductionmentioning
confidence: 99%